2013
DOI: 10.1080/01446193.2012.736026
|View full text |Cite
|
Sign up to set email alerts
|

Strategic planning in construction professional service firms: a study of Irish QS practices

Abstract: The role and usefulness of strategic planning has been documented over several decades of strategic management research. Despite the significant body of existing knowledge in the field of strategic planning, there remains limited empirical investigation of the construction sector, specifically professional service firms operating within it. The construction sector is hugely important to the Irish economy, yet until now, no empirical investigation has been undertaken to determine the strategic planning process … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 35 publications
2
12
0
1
Order By: Relevance
“…For construction contractor firms, process formality is correlated to firm size (Price et al 2003) and ownership structure (Dansoh 2005), in addition to an organizational type. Limited evidence exists within a construction context of organizational types about QS practices save for the earlier study (Murphy 2013) and as noted, the external environment facing these firms has changed significantly since the earlier study was undertaken.…”
Section: Theoretical Backgroundmentioning
confidence: 93%
See 3 more Smart Citations
“…For construction contractor firms, process formality is correlated to firm size (Price et al 2003) and ownership structure (Dansoh 2005), in addition to an organizational type. Limited evidence exists within a construction context of organizational types about QS practices save for the earlier study (Murphy 2013) and as noted, the external environment facing these firms has changed significantly since the earlier study was undertaken.…”
Section: Theoretical Backgroundmentioning
confidence: 93%
“…They found that the strategic management process varied systematically with the degree of "rational" and "adaptive" planning characteristics concluding that firms have different strategic decision-making profiles. Using similar process features, the earlier study of Irish QS practices (Murphy 2013) ascertained these characteristics, and the existence of clusters of QS practices, akin to strategic groups, were identified based on not only process characteristics, but also the resulting strategic choices made.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 2 more Smart Citations
“…Khan, Flanagan, and Lu (2016) describe how different interdependencies between activities at the construction site and in the CSC affects the performance of both the supply chain and the construction process. Such dependence stems from the suppliers' need to adapt delivery schedules, components and quantities in accordance with the progress of production and changes in the process (Shin et al 2011), as well as what on-site conditions may affect delivery options (Murphy 2013). Doloi (2009) notes that information sharing between the construction process and the actors in the CSC leading to a better chance of the building object being delivered on time and at the right quality to developer.…”
Section: The Need Of Information Sharing In Construction Supply Chainsmentioning
confidence: 99%